2022
DOI: 10.3920/jiff2021.0076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, size, and sex on adult black soldier fly [Hermetia illucens L. (Diptera: Stratiomyidae)] thermal preference

Abstract: Population growth and rapid urbanisation have increased the global demand for animal feed and protein sources. Therefore, traditional animal feed production should be increased through the use of alternative nutrient sources. Insects as feed are beginning to fill this need. One such insect is the black soldier fly, Hermetia illucens L. (Diptera: Stratiomyidae). However, to more effectively mass produce the black soldier fly, a better understanding of its thermal biology is needed. Thus, the aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…Studies of critical thermal maxima suggest that 44-46 °C is lethal for adults (Laursen et al, 2021). Age and size (but not sex) determined preferred temperature for adults: young adults (1 day after eclosion) preferred warmer temperatures (28.7 °C) than 7-day-old adults (19.2 °C), while smaller adults preferred cooler temperatures than larger adults (Addeo et al, 2021). Notably, adults were not fed in Addeo et al (2021); thus, negative correlations between age and preferred temperature may be related to reducing metabolic rate under starvation conditions, and this result should be re-examined with fed adults.…”
Section: Temperaturementioning
confidence: 98%
See 1 more Smart Citation
“…Studies of critical thermal maxima suggest that 44-46 °C is lethal for adults (Laursen et al, 2021). Age and size (but not sex) determined preferred temperature for adults: young adults (1 day after eclosion) preferred warmer temperatures (28.7 °C) than 7-day-old adults (19.2 °C), while smaller adults preferred cooler temperatures than larger adults (Addeo et al, 2021). Notably, adults were not fed in Addeo et al (2021); thus, negative correlations between age and preferred temperature may be related to reducing metabolic rate under starvation conditions, and this result should be re-examined with fed adults.…”
Section: Temperaturementioning
confidence: 98%
“…Adult size is closely linked to larval feeding (e.g. Addeo et al, 2021). Adult male and female flies look similar, though males are often smaller in body size (Jones and Tomberlin, 2019).…”
Section: Black Soldier Fly Biologymentioning
confidence: 99%
“…[46] How mate choice emerges at the population level has not been explicitly explored, but it seems reasonable that bottom-up processes such as these are what lead to the formation of mating aggregations that have been described as "leks" [37] (Figure 3); although we note that the accuracy of this descriptor is not readily apparent for flies in a colony setting, and its use within the Insecta as a whole has been debated. [16] That said, the understanding of mechanisms underlying communication and mate choice within H. illucens are still putative and little is known within the scientific literature about how adult black soldier flies exchange information or navigate within their broader environment or which has been gleaned from relatively few experiments investigating abiotic factors, [40,51,52] varied oviposition substrates, [53,54] and trap materials. [12,28,55,56] Moreover, none is known of the specific mechanisms of how they might achieve long-distance travel to and from wild lekking sites, [37] such as hilltopping, utilizing search images, following conspecifics, or photo-and phonotaxis.…”
Section: Communication and Courtshipmentioning
confidence: 99%
“…That said, the understanding of mechanisms underlying communication and mate choice within H . illucens are still putative and little is known within the scientific literature about how adult black soldier flies exchange information or navigate within their broader environment or which has been gleaned from relatively few experiments investigating abiotic factors, [ 40,51,52 ] varied oviposition substrates, [ 53,54 ] and trap materials. [ 12,28,55,56 ] Moreover, none is known of the specific mechanisms of how they might achieve long‐distance travel to and from wild lekking sites, [ 37 ] such as hilltopping, utilizing search images, following conspecifics, or photo‐ and phonotaxis.…”
Section: Communication and Courtshipmentioning
confidence: 99%
“…Studies have shown that the reproductive performances of H. illucens are influenced by many factors in the breeding environment, such as temperature [ 55 , 56 ], light [ 57 , 58 , 59 ], humidity [ 60 ], attractive substrate for stimulating ovipositing [ 50 , 61 , 62 ], ovipositing conditions [ 63 , 64 ], etc. The economic efficiency of the rearing and reproduction of this species is therefore greatly influenced by the most detailed knowledge of the particularities of the reproductive process.…”
Section: Introductionmentioning
confidence: 99%